2016
DOI: 10.1177/2010105815624121
|View full text |Cite
|
Sign up to set email alerts
|

Living with heart failure: Perspectives of patients from Singapore

Abstract: Introduction: Heart failure is a progressive and often incurable condition associated with a poor quality of life. The aim of this study was to understand the experiences and preferences regarding care, communication and decision-making among patients living with heart failure in Singapore. Methods: Five focus groups were conducted with 27 patients that had heart failure. The focus groups were audio-recorded and transcribed verbatim. Thematic analysis was used for analyzing transcripts. Results: Six themes rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…In another study, it was shown that limitations in physical activities, mental disorders such as anxiety, and lack of knowledge about the disease can negatively affect QoL of these patients and it was proposed that the patient education be done to alleviate these problems (Malhotra et al 2016). Similar to our study which indicated the QoL improvement in the psychological aspect, McCorkle et al (2011) reported that self-management training in patients with cancer could improve the management of the symptoms and reduce their anxiety and psychological problems in different courses of treatment and even after treatment, and consequently enhance patients' QoL.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was shown that limitations in physical activities, mental disorders such as anxiety, and lack of knowledge about the disease can negatively affect QoL of these patients and it was proposed that the patient education be done to alleviate these problems (Malhotra et al 2016). Similar to our study which indicated the QoL improvement in the psychological aspect, McCorkle et al (2011) reported that self-management training in patients with cancer could improve the management of the symptoms and reduce their anxiety and psychological problems in different courses of treatment and even after treatment, and consequently enhance patients' QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Living with HF means living with a failing heart and a body that is both unreliable and unpredictable . When the body's condition changes constantly, when it is weak, fragile, and vulnerable, it reminds the person that life is finite.…”
Section: Resultsmentioning
confidence: 99%
“…Stable periods are interrupted by rapid deteriorations in heart‐function, often life‐threatening. The main physical symptoms consist of fatigue and breathlessness, which may limit exercise tolerance . In addition to physical limitations, there are also extensive social and existential consequences .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations